Profitability Analysis in Halal Food and Beverage Industry Manufacturing Companies in Asian Countries (Malaysia, Indonesia, Turkey, Bahrain) - Devi Yolanda Oktavia; Agus Sukoco; Joko Suyono (Finance : International Journal of Management Finance, 2025)
Indonesia, Malaysia, Bahrain, Turkey are 4 countries in Asia where the majority are Muslims. Indonesia, Malaysia, Bahrain, Turkey have great opportunities to develop quality and quantity in the halal industry. There are several issues currently faced in the development of the halal industry in Indonesia, Malaysia, Bahrain, and Turkey, including infrastructure development, halal assurance systems, and increasing halal contribution to the trade balance. The research methodology is a descriptive analysis method used to measure and collect profitability information on financial statements during the 2019-2023 period carefully and efficiently so that it can be used as a guideline in carrying out research. Types of Data are data that research finds through information or information obtained, as well as finding the right solution to analyze the problems faced or find out the existing problems. The results of the study show that financial performance is in the category of not good from profitability from a profitability.